Neuronal Mitophagy: Friend or Foe? - Doxaki, Christina; Palikaras, Konstantinos (Frontiers in Cell and Developmental Biology, 2021)
Maintenance of neuronal homeostasis is a challenging task, due to unique cellular organization and bioenergetic demands of post-mitotic neurons. It is increasingly appreciated that impairment of mitochondrial homeostasis represents an early sign of neuronal dysfunction that is common in both age-related neurodegenerative as well as in neurodevelopmental disorders. Mitochondrial selective autophagy, known as mitophagy, regulates mitochondrial number ensuring cellular adaptation in response to several intracellular and environmental stimuli. Mounting evidence underlines that deregulation of mitophagy levels has an instructive role in the process of neurodegeneration. Although mitophagy induction mediates the elimination of damaged mitochondria and confers neuroprotection, uncontrolled runaway mitophagy could reduce mitochondrial content overstressing the remaining organelles and eventually triggering neuronal cell death. Revealing the molecular mechanisms of neuronal mitophagy and its intricate role in neuronal survival and cell death, will assist in the development of novel mitophagy modulators to promote cellular and organismal homeostasis in health and disease.